Primary esophageal melanoma: features of diagnosis and treatment - B. V. Sigua; S. Yu. Rakita; A. S. Kachiuri; D. V. Gurzhy; A. V. Belyaeva; V. P. Zemlyanoy (Вестник хирургии имени И.И. Грекова)
Primary esophageal melanoma is a rare and extremely aggressive malignant neoplasm originating from mucosal melanocytes. The complex histological structure of the tumor, which in 10–25 % of cases may not contain melanin characteristic of these formations, leads to a high frequency of diagnostic errors, reaching 50 %. Immunohistochemical examination is the standard for diagnosing the disease. Primary esophageal melanoma is a tumor with a high potential for hematogenous and lymphogenous metastasis. So, when the tumor spreads to the submucosa, the frequency of locoregional metastasis reaches 54 %. Radical surgery in combination with adjuvant methods of treatment improves the results of treatment in this category of patients. Immunotherapy is a promising method of complex treatment, but requires further study.